Legal Review of the Implementation of Informed Consent in Genomic Research in Indonesia Case Study of Health Biotechnology Research - Haryono, Tri Agus; Rosidah, Rosidah; Permana, Diki; Bunyamin, Bubun; Yuliarpan, Pipit; Kurniati, Yeti (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to explore and analyze the implementation of informed consent in the context of genomic research in Indonesia, and provide recommendations for future improvements. Through a legal analysis and case study approach, this research identifies factors that influence the effectiveness of informed consent and its impact on the protection of research subjects. The methods used in this research include literature analysis and case studies to gain a comprehensive understanding of the issue. The results show that in the development of genomic research, there has been encouraging progress but there is still a lack of adequate understanding and implementation of IC. A legal review of the implementation of informed consent in genomic research in Indonesia is an increasingly relevant topic as health biotechnology technology develops.